Advanced Empathy: A Key to Supporting People Experiencing Psychosis or Other Extreme States - Richard Lakeman (Psychotherapy and Counselling Journal of Australia)
The capacity to be empathic and communicate empathically are foundational skills of counselling and psychotherapy, if not all interpersonal helping endeavours. Empathy requires the capability, inclination, and capacity to take the perspective of others, appraise and understand their experiences without being overwhelmed, and communicate this understanding in a helpful way to them. This paper reviews and highlights the importance of this capability and describes a form of "advanced empathy" characterised by the capacity to take the perspective of others experiencing extreme states, making sense of these experiences, and conveying an understanding of their experiences in a way which is useful to them. The capacity for advanced empathy is a foundation for any kind of therapeutic work with people who may express delusional or disturbing ideas and will be helpful for anyone needing to develop or maintain a relationship with people in extreme states. These ideas have been tested in practice and with a wide variety of audiences. This synthesis provides practical advice that may be useful for training, supervision, or reflection by those who hope to build alliances with people in crisis, experiencing psychosis, or who are otherwise "out of step" with people around them.